Contract farming and land tenancy in Indian agriculture - Kumar, Pramod; Manjunatha; A V; Sourav, Suman K; Manjunatha; A V; Sourav, Suman K (New Delhi Sage, 2021)
Contract Farming and Land Tenancy in Indian Agriculture explores key determinants that drive contractual/lease relationships through the examples of various existing arrangements in the country. It is based on the premise that contract farming or leasing can be an attractive option to policy makers keen on integrating the poor into the industrialized sector of the economy by helping them access the gains from trade that characterize successful agricultural tenancy arrangements. Agricultural diversification can be promoted through a favourable environment of policy support in the area of contract farming and by reforming land policies that will enhance the bargaining power of small holders. The book systematically analyses contract farming in the broader framework of existing land and lease market system. It contains cross-sectional assessment with field insights from various states. The book will help to formulate a strong policy in favour of stakeholders involved in contract farming and land tenancy in India.
Keywords: Contract farming-India; Land Tenancy; Agriculture-India